1980
DOI: 10.1126/science.210.4468.399
|View full text |Cite
|
Sign up to set email alerts
|

Saline Culture of Crops: A Genetic Approach

Abstract: Increasing salinity of soil and water threatens agriculture in arid and semiarid regions. By itself, the traditional engineering approach to the problem is no longer adequate. Genetic science offers the possibility of developing salt-tolerant crops, which, in conjunction with environmental manipulation, could improve agricultural production in saline regions and extend agriculture to previously unsuited regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
233
0
14

Year Published

1983
1983
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 577 publications
(252 citation statements)
references
References 35 publications
5
233
0
14
Order By: Relevance
“…Salt induces osmotic stress by preventing absorption of water from soil and the result is the increase of the concentration of the potentially toxic salt ions within plant cells. In order to overcome the deleterious effects of soil salinity on yields of crops, the development of salt tolerant varieties is critically important (Epstein et al 1980) Many studies on seed germination and growth under salinity have shown that seeds reach their best germination rate and seedling development in non-saline media and are very sensitive to the elevation of salinity in the milieu which causes reduced germination rate, low chlorophyll content and poor growth (Qados et al 2011;Cokkizgin 2012;Mena et al 2015). Salinity tolerance is defined as the ability of plants to continuously grow under salt stress conditions (Munns 2002).…”
Section: Study Site and Plant Materialsmentioning
confidence: 99%
“…Salt induces osmotic stress by preventing absorption of water from soil and the result is the increase of the concentration of the potentially toxic salt ions within plant cells. In order to overcome the deleterious effects of soil salinity on yields of crops, the development of salt tolerant varieties is critically important (Epstein et al 1980) Many studies on seed germination and growth under salinity have shown that seeds reach their best germination rate and seedling development in non-saline media and are very sensitive to the elevation of salinity in the milieu which causes reduced germination rate, low chlorophyll content and poor growth (Qados et al 2011;Cokkizgin 2012;Mena et al 2015). Salinity tolerance is defined as the ability of plants to continuously grow under salt stress conditions (Munns 2002).…”
Section: Study Site and Plant Materialsmentioning
confidence: 99%
“…Studies have been mainly focused salinity is aggravated in coastal areas where urban on the reproductive biology of the genus (Campbell, and industrial consumption of water can often result 1915;1922;Armenise, 1957). More recently, the in seawater being drawn into groundwater supply breeding characteristics and pollen production of P. (Epstein et al, 1980). Therefore, soil salinity is /afz/o/m and P. an^Ms^i/o/m were investigated (Lepart sometimes a key factor in determining the ecological & Dommee, 1992; Aronne & Wilcock, 1992;1993).…”
mentioning
confidence: 99%
“…Os calos embriogênicos a nível celular são compostos, em sua maioria, por células meristemáticas com dimensões relativamente pequenas e com citoplasma denso (Tomes, 1985). Em milho, estes calos são classificados como calos compactos ou do tipo I, como relatado em nosso trabalho, e calos friáveis ou do tipo II (Green et al, 1983;Armstrong & Green, 1985). Estes mesmos autores comentam que o tipo de calo está relacionado com a idade do embrião, o genótipo e principalmente com a concentração de sacarose e prolina no meio.…”
Section: Resultsunclassified
“…A crescente salinização do solo e da água ameaça a agricultura de zonas áridas e semi-áridas, bem como de outras regiões do mundo (Epstein et al, 1980). Plantas cultivadas em ambientes com excesso de NaCl apresentam primeiramente uma inibição no crescimento, freqüentemente acompanhada pela presença de áreas necrosadas nas folhas.…”
Section: Introductionunclassified